Prediction of computer vision syndrome by video game addiction in Chinese and Spanish students - Luis- Lucio Lobato Rincón; Maria Ángeles Medina Sánchez; Pilar Huerta Zavala; Rafael Fabricio Matos Cámara; Ricardo Bernárdez Vilaboa (Revista Habanera de Ciencias Médicas)
Introduction: The use of video games, due to the extent that it has reached during the COVID-19 pandemic, is a relevant study variable especially because of its interactions with aspects of mental and visual health.